2023
DOI: 10.3389/fpubh.2023.1126126
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aquatic exercises on physical fitness and quality of life in postmenopausal women: an updated systematic review and meta-analysis

Abstract: ObjectiveIn the present systematic review and meta-analysis, we aimed to evaluate and update the effects of aquatic exercise on physical fitness and quality of life (QoL) in postmenopausal women.MethodsThe databases Cochrane Library, PubMed, Web of Science, and MEDLINE were searched for randomized controlled trials (RCTs) on the topic from inception to July 2022. The GetData software was used to extract data from the published images. RevMan5.4 software was used for statistical analysis. Data are expressed as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 93 publications
0
1
0
Order By: Relevance
“…Nevertheless, there have been debates on using hormone therapy 8 . As alternative treatments for perimenopausal symptoms, practitioners have suggested that long persistent periods of 3 to 10 years of perimenopause syndrome may need nonpharmacological support such as psychotherapy, exercise, and music therapy 9-11 …”
mentioning
confidence: 99%
“…Nevertheless, there have been debates on using hormone therapy 8 . As alternative treatments for perimenopausal symptoms, practitioners have suggested that long persistent periods of 3 to 10 years of perimenopause syndrome may need nonpharmacological support such as psychotherapy, exercise, and music therapy 9-11 …”
mentioning
confidence: 99%